Monetary policy transmission in the euro area: What do aggregate and national structural models tell us? - Peter J. A. van Els; Alberto Locarno; Julian Morgan; Jean-Pierre Villetelle (European Central Bank (ECB), 2001)
This paper analyses the monetary transmission mechanism in the euro area through the use of large scale macroeconomic models at the disposal of the European Central Bank and the National Central Banks of the Eurosystem. The results reported are based on a carefully designed common simulation experiment involving a 100 basis point rise in the policy interest rate for two years accompanied by common assumptions regarding the path of long-term interest rates and the exchange rate. Aggregating the country level results, the fall in output is found to reach a maximum of 0.4% after 2 years. The maximum aggregate fall in prices is also 0.4%, but it occurs 2 years later. The dominant channel of transmission in the first two years is the exchange rate channel, but in terms of the impact on output, the user cost of capital channel becomes dominant from the third year of the simulation onwards
Keywords: C50; E17; E5; 330; macroeconomic models; Monetary policy transmission mechanism